2012
DOI: 10.1088/1468-6996/13/6/064103
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxylapatite nanoparticles: fabrication methods and medical applications

Abstract: Hydroxylapatite (or hydroxyapatite, HAp) exhibits excellent biocompatibility with various kinds of cells and tissues, making it an ideal candidate for tissue engineering, orthopedic and dental applications. Nanosized materials offer improved performances compared with conventional materials due to their large surface-to-volume ratios. This review summarizes existing knowledge and recent progress in fabrication methods of nanosized (or nanostructured) HAp particles, as well as their recent applications in medic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
62
0
7

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 126 publications
(70 citation statements)
references
References 358 publications
(355 reference statements)
1
62
0
7
Order By: Relevance
“…This result is in good agreement with previous studies that have shown polymeric vial along with zirconia balls is an appropriate milling media to annihilate contamination problems and to achieve modified morphologies with high biomedical performance [17,25,28]. Figure 3 shows the XRD profile and schematic view of CaHPO 4 , Ca(OH) 2 and CaF 2 powder mixture in the presence of 20 wt% TiO 2 after the beginning of milling.…”
Section: Sem-edx and Tem Analysissupporting
confidence: 89%
See 4 more Smart Citations
“…This result is in good agreement with previous studies that have shown polymeric vial along with zirconia balls is an appropriate milling media to annihilate contamination problems and to achieve modified morphologies with high biomedical performance [17,25,28]. Figure 3 shows the XRD profile and schematic view of CaHPO 4 , Ca(OH) 2 and CaF 2 powder mixture in the presence of 20 wt% TiO 2 after the beginning of milling.…”
Section: Sem-edx and Tem Analysissupporting
confidence: 89%
“…From Fig. 4(a), all the sharp characteristic peaks corresponding to Ca(OH) 2 and CaF 2 disappear completely after 5 h of milling. Also several characteristic peaks corresponding to CaHPO 4 vanish and a number of new broadened peaks belonging to FAp emerge especially between 2θ = 31°-34°.…”
Section: Phase Analysismentioning
confidence: 99%
See 3 more Smart Citations